FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG DI KELURAHAN KAWANGKOAN BAWAH KECAMATAN AMURANG BARAT KABUPATEN MINAHASA SELATAN - Yiska Dea Sumampow; Ribka Magdalena Kumaat; Gene Henfried Meyer Kapantow (Sam Ratulangi University, 2021)
This study aims to determine which factors that influence corn production in the Kawangkoan Bawah Sub-District, Amurang Barat District, South Minahasa Regency. This research was conducted from June to September 2021. The data collected in this study were primary data in the form of dialogue with informants and respondents and secondary data obtained from previous research and literature. Analysis of the data used in this study using multiple linear regression method, with the Cobb-Douglas production function model. The results showed that the variables of planting area, seeds, urea fertilizer, ponska fertilizer, labor, and pesticides simultaneously affected the amount of corn production in Kawangkoan Bawah Village, Amurang Barat District and partially the factors that affected production. corn at = 5% is the land area factor (X1) and the seed factor (X2).